The Growing Impact of Niobium in Organic Synthesis and Catalysis - Lacerda, Valdemar; Santos, Deborah Araujo dos; Silva Filho, Luiz Carlos da [UNESP]; Greco, Sandro Josá; Santos, Reginaldo Bezerra dos (Aldrich Chemical Co Inc, 2012)
The growing interest in, and applications of, niobium compounds in organic synthesis and catalysis are surveyed, with a focus on their efficiency and versatility in several classical and broad organic reaction types. It is our hope that this review will spur further investigations of this lesser studied, but equally important, member of group 5 transition metals.
Keywords: catalysis; organic synthesis; niobium chlorides; niobium oxides; selectivity; versatility; efficiency